2022
DOI: 10.3846/tede.2022.16325
|View full text |Cite
|
Sign up to set email alerts
|

The Need of a New Management Regarding the Contradictory East-West European Capital and Labour Flows. A Regional Welfare Approach

Abstract: The paper addresses an extremely current phenomenon: migration in opposite directions of FDI and labour, in context with the permanent need for economic growth and welfare. The analysis is carried out over a period of 12 years, in the context of setting objectives and working hypotheses regarding the realization of a correlation model of phenomena and optimization of migration flows in order to obtain welfare through economic development. The results of the research will reflect the relevance of the aggregatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The practice of recent years has shown that this means mobility for employment and postgraduate training, starting from the residency period in more economically developed countries, with financial potential and/or adequate funding sources. From the perspective of the last two decades, we can appreciate that we are facing an exodus of specialists from healthcare units [ 16 , 17 ] with shortages of equipment and funding (from less developed countries), with already chronic imbalances in the employment of the medical sector [ 18 ], to medical units that offer the prospect of the future in excellence in health services, i.e., the smart association of technological transfer progress [ 19 ] with financial comfort through employment (so-called “decent employment”). Additionally, modern medicine has come to build a necessary balance between prevention and intervention as a form of efficiency for the quality of healthy life.…”
Section: Introductionmentioning
confidence: 99%
“…The practice of recent years has shown that this means mobility for employment and postgraduate training, starting from the residency period in more economically developed countries, with financial potential and/or adequate funding sources. From the perspective of the last two decades, we can appreciate that we are facing an exodus of specialists from healthcare units [ 16 , 17 ] with shortages of equipment and funding (from less developed countries), with already chronic imbalances in the employment of the medical sector [ 18 ], to medical units that offer the prospect of the future in excellence in health services, i.e., the smart association of technological transfer progress [ 19 ] with financial comfort through employment (so-called “decent employment”). Additionally, modern medicine has come to build a necessary balance between prevention and intervention as a form of efficiency for the quality of healthy life.…”
Section: Introductionmentioning
confidence: 99%